Estimating the optimal market price to sell an apartment - Abreu, Carlos Alexandre Camargo de (2018)
This paper demonstrates an investment economic analysis model based on Real Option Valuation Theory applied to decision-making of individual real estate investors. The model captures the valuation of flexibilities caused by expected market trend and uncertainty and offers an optimized value for the investment opportunity. A Real Option for investment delay is used applied to the case of postponing the selling of an apartment until the estimated “best” optimal market price and option value. Application of the model is made using market data from three Brazilian major cities’ real estate market. As an important finding we have the estimation of an expanded Net Present Value for the investment when apartment selling is exercised at the optimal market price defined. It is possible to use this model to forecast what would be the optimal price and moment to sell an apartment in an investor point of view.